Türkçede güdü ve duygu göstergeleri : ünlemler - Akkaş, Şeyma Nur (My University, 2025)
Türkçede güdü ve duygu göstergeleri : ünlemler Bu çalışmada, Türkiye Türkçesinde duyguların ifadesinde kullanılan dilsel araçlar olarak ünlemler eş zamanlı bakış açısıyla incelenmektedir. Duygular, insanların yaşamları boyunca varlığını sürdüren ruhsal hareketlerdir. Duyguları yansıtmada uzmanlaşmış (spesifik) dilsel araçlar ise ünlemlerdir. Ünlemler, esas işlevi duygu ve güdüleri bildirmek olan, geçici olarak farklı işlevler de üstlenebilen sözcük birimleridir. Çalışmada öncelikle duygu kavramı ele alınmakta; güdü, his, heyecan ve algı gibi ilgili kavramlar incelenmekte; duygunun güdü, duyu ve kültürle ilişkisine değinilmekte; çalışmanın dayanak noktalarından biri olan duygu sınıflandırmalarına da yer verilmektedir. Bu bağlamda özellikle birincil (temel) duyguların tespiti ve sınıflandırılması üzerinde durulmaktadır. Duygular ve onların sınıflandırması üzerine birçok çalışma vardır. Bu çalışmada birincil ve ikincil duyguların tespiti hususunda Robert Plutchik’in duygu çarkıfeleğinden yararlanılmaktadır. Plutchik, sekiz temel duygunun belirli kombinasyonlarla çok sayıda yeni duygu oluşturduğunu savunur ve iki temel duygunun birleşiminden oluşanlara “birincil ikililer” adını verir. Örneğin, birincil duygular olan sevinç ve kabullenmenin birleşimi sevgiye, tiksinti ve öfkenin birleşimi ise nefrete dönüşür. Plutchik’in yaklaşımı, ünlemlerin hem yapısal hem de işlevsel yönleriyle değerlendirme imkânı sunmaktadır. Plutchik’in birincil ve ikincil duygular ayrımının Türkçe ünlemlere uygulanması, ünlemlerin bildirdiği duyguları belirlemede çalışmanın kuramsal zeminini oluşturmaktadır. Bu çalışmada ünlemler, birincil ve ikincil ünlemler olarak sınıflandırılmaktadır. a!, ah!, ay!, bre!, e!, ıh!, ıy!, o!, of! / öf, oh!, oy!, peh (peh)!, vah! vb. birincil ünlemler; hiç anlamları olmayan, refleksif ve doğrudan duygu bildiren sözcük birimleridir. İkincil ünlemler ise arka planda anlamları sezilen; aman (aman)!, ayol!, (h)eyvah!, imdat, hoppala!, lan! ~ ulan!, sakın (ha)!, yazık! / heyhat!, Allah aşkına!, aşk olsun!, bana bak! / baksana!, daha (da) neler!, hiç öyle şey olur mu! ~ (hiç) öyle şey mi olur!, ne alaka! / kelalaka!, ne münasebet!, oh olsun!, yok artık! gibi ünlemlerdir. İkincil ünlemlerin anlamları sezilse de bu anlamlar ikinci derecelidir. Onların da temel işlevi, birincil ünlemler gibi, güdü ve duyguları dile getirmektir. İkincil ünlemler, çalışmada kuruluşları/ yapıları açısından üç türe -kelime ve kelime şekli yapısında olanlar, öbek yapısında olanlar ve cümle yapısında olanlar- ayrılıp birincil ve ikincil işlevlerine göre incelenmektedir. VII nde ünlem, birincil ünlem, ikincil ünlem, duygu, güdü, birincil (temel) duygular, ikincil (öz bilinçli) duygular.

In this study, interjections used as linguistic tools for expressing emotions in Turkey Turkish are examined from a synchronic perspective. Emotions are mental movements that persist throughout people's lives. The linguistic tools specialized in reflecting emotions are interjections. Interjections are word units whose primary function is to convey emotions and impulses, although they may temporarily take on other functions. The study first addresses the concept of emotion; examines related concepts such as impulse, feeling, excitement, and perception; discusses the relationship of emotion with impulse, sensation, and culture; and includes classifications of emotions, which form one of the foundations of the study. In this context, particular emphasis is placed on the identification and classification of primary (basic) emotions. There are many studies on emotions and their classification. In this study, Robert Plutchik’s emotion wheel is used for identifying primary and secondary emotions. Plutchik argues that eight basic emotions combine in specific ways to form many new emotions, and he names the combinations of two basic emotions as “primary dyads.” For example, the combination of the primary emotions joy and acceptance results in love, while the combination of disgust and anger results in hatred. Plutchik’s approach provides a framework for evaluating interjections both structurally and functionally. The application of Plutchik’s distinction between primary and secondary emotions to Turkish interjections constitutes the theoretical basis of the study in determining the emotions expressed by interjections. In this study, interjections are classified as primary and secondary interjections. Interjections such as a!, ah!, ay!, bre!, e!, ıh!, ıy!, o!, of! / öf!, oh!, oy!, peh (peh)!, vah! etc., are primary interjections; they are word units that do not have any lexical meaning, are reflexive, and directly express emotion. Secondary interjections, on the other hand, are those in which meanings can be sensed in the background; such as aman (aman)!, ayol!, (h)eyvah!, imdat!, hoppala!, lan! ~ ulan!, sakın (ha)!, yazık! / heyhat!, Allah aşkına!, aşk olsun!, bana bak! / baksana!, daha (da) neler!, hiç öyle şey olur mu! ~ (hiç) öyle şey mi olur!, ne alaka! / kelalaka!, ne münasebet!, oh olsun!, yok artık! etc. Although the meanings of secondary interjections can be sensed, these meanings are secondary. Like primary interjections, their main function is to express emotions and impulses. In this study, secondary interjections are categorized into three types based on their structure: those in the form of words and word IX forms, those in the form of phrases, and those in the form of sentences, and they are analyzed according to their primary and secondary functions. Interjections in Turkey Turkish, primary interjection, secondary interjection, emotion, motivation, primary (basic) emotions, secondary (self-conscious) emotions.
Keywords: duygular Turkish language; emotions; interjections; Öğrenim ve öğretim; Study and teaching; Turkish language; Türk dili; ünlemler